2007
DOI: 10.1097/01.nmc.0000281959.71454.e5
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Fatigue and Evidence-Based Interventions

Abstract: The aim of this article is to review postpartum fatigue, especially as it relates to the occurrence and pathophysiology of three common postpartum conditions known to contribute to fatigue: anemia, infection/inflammation, and thyroid dysfunction. Fatigue is an unrelenting condition that affects physical and mental health, and it has implications for everyday activities, motivation, and social interactions. Although individuals of all ages and both genders are at risk for developing fatigue, postpartum fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…(19) Montazeri et al studied the content validity of the Persian version of the EPDS and reported an r-value of 0.77 for its test-retest reliability. (20) Since there is documented evidence that anaemia can result in fatigue, (12) a complete blood count was performed four weeks after delivery for all the women in both groups to diagnose postpartum anaemia. Other information, including the demographics of the participants, was collected at the time of enrollment into the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(19) Montazeri et al studied the content validity of the Persian version of the EPDS and reported an r-value of 0.77 for its test-retest reliability. (20) Since there is documented evidence that anaemia can result in fatigue, (12) a complete blood count was performed four weeks after delivery for all the women in both groups to diagnose postpartum anaemia. Other information, including the demographics of the participants, was collected at the time of enrollment into the present study.…”
Section: Methodsmentioning
confidence: 99%
“…(5) Other undesirable and potentially serious outcomes include termination of lactation, (11) impairment of the sexual relationship between spouses, (7) development of stress and mood disorders (5) and an increased risk of postpartum depression. (12) Therefore, it is of utmost importance that an effective solution to this condition is found. There has been some evidence supporting the positive effect of physical exercise on maternal and infant health.…”
Section: Introductionmentioning
confidence: 99%
“…These requirements are likely to be more difficult to do when a mother is either depressed or extremely fatigued. However, except for the postpartum period when many mothers experience fatigue (Corwin and Arbour 2007;Runquist 2007), previous research has neglected the role that maternal fatigue might play in parenting and child outcomes. While there has been some recent research that has examined sleep problems of children and how that impacts their parents (Bell and Belsky 2008;Lee et al 2007;Meltzer and Mindell 2007;Mindell et al 2009), we understand very little about how maternal fatigue influences parenting.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited research has examined the role of fatigue in regard to parenting. The minimal research that has been conducted was either associated with maternal sleep deprivation (Corwin and Arbour 2007;Runquist 2007;Meltzer and Mindell 2007) or with women who have chronic illnesses. In these cases, fatigue was either implied or a frequent symptom of the illness (Helseth and Ulfsaet 2005;Deatrick et al 1998;Thorne 1990;White et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation